2017
DOI: 10.3390/agronomy7010018
|View full text |Cite
|
Sign up to set email alerts
|

Plant Responses to Salt Stress: Adaptive Mechanisms

Abstract: This review deals with the adaptive mechanisms that plants can implement to cope with the challenge of salt stress. Plants tolerant to NaCl implement a series of adaptations to acclimate to salinity, including morphological, physiological and biochemical changes. These changes include increases in the root/canopy ratio and in the chlorophyll content in addition to changes in the leaf anatomy that ultimately lead to preventing leaf ion toxicity, thus maintaining the water status in order to limit water loss and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

29
673
1
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,124 publications
(712 citation statements)
references
References 218 publications
(333 reference statements)
29
673
1
9
Order By: Relevance
“…The metabolic conditions of marine phytoplankton resulting from steady-state hyper-and hyposaline stresses are relatively unknown, as most previous studies have focused on euryhaline species or nonsteady-state responses to osmotic shock (Qasim et al, 1972;Macler, 1988;Jahnke & White, 2003;Bussard et al, 2017). Extreme salinity stress is however well known to induce oxidative stress (Jahnke & White, 2003;Acosta-Motos et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The metabolic conditions of marine phytoplankton resulting from steady-state hyper-and hyposaline stresses are relatively unknown, as most previous studies have focused on euryhaline species or nonsteady-state responses to osmotic shock (Qasim et al, 1972;Macler, 1988;Jahnke & White, 2003;Bussard et al, 2017). Extreme salinity stress is however well known to induce oxidative stress (Jahnke & White, 2003;Acosta-Motos et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…ID was also reported to be a potential growth retardant as observed in flax (Salama et al ) and maize (Kanai et al ). Acosta‐Motos et al () have reported that salinity can enhance the root to shoot ratio because the roots store high amount of toxic ions under saline conditions and the translocation of nutrients to shoot is hampered so as to protect it. For example, in different studies, salt‐induced enhanced root to shoot ratio has been observed, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Acosta‐Motos et al () have reported that NO is involved in the plant responses to saline conditions. In the present study, stress conditions decreased the NO contents of strawberry plants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The accumulation of these ions derives from low-quality irrigation water and poor soil drainage [71]. Salinity reduces plant growth and yield when the concentration of salts reaches 4 dS/m.…”
Section: Salinity Stressmentioning
confidence: 99%